34.3k views
5 votes
Using the reminder therom 4x^3+6x^2+3x+2 is divided by 2x + 3​

1 Answer

3 votes

Answer:

-5/2 or -2.5.

Explanation:

The remainder theorem states that if the polynomial f(x) is divided by (x - a) then the remainder is f(a).

To find the remainder we put x = -3/2 ( by solving 2x + 3 = 0).

The remainder = 4(-3/2)^3 + 6(-3/2)^2 + 3(-3/2) + 2

= -27/2 + 27/2 - 9/2 + 2

= -9/2 + 4/2

= -5/2.

User Hokhy Tann
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.